Experience Design for Community-Based Tourism Through Creative Tourism Activities Based on BCG Economy Model: A Quantitative Study of Koh Kret, Nonthaburi - Phoncharoen, Kannika (International Journal of Multidisciplinary in Management and Tourism, 2025)
This research aims to examine how experience design for community-based tourism (CBT) through creative tourism activities based on the Bio-Circular-Green (BCG) Economy Model influences tourist satisfaction and behavioral intentions in Koh Kret, Nonthaburi. The study specifically investigates three key components of experience design: local capital utilization, local interpreter engagement, and five-senses integration. Using a quantitative approach, data were collected from 385 tourists visiting Koh Kret through systematic random sampling. Statistical analyses included descriptive statistics, confirmatory factor analysis, and structural equation modeling. Results revealed that all three experience design dimensions significantly influenced tourist satisfaction (R² = 0.731) and behavioral intentions (R² = 0.689), with five-senses integration demonstrating the strongest effect (β = 0.412), followed by local capital utilization (β = 0.385) and local interpreter engagement (β = 0.337). The findings provide empirical evidence that BCG-aligned experience design enhances CBT sustainability while creating memorable tourist experiences. This study contributes to tourism design theory by offering an integrated framework connecting BCG principles with sensory-rich tourism experiences, providing practitioners with actionable strategies for sustainable tourism development that balances economic benefits with environmental and cultural preservation.